Videothoracoscopic Right Pneumonectomy for Destroyed Lung - İlker Kolbaş; Çağatay Tezel; Serdar Evman; Serkan Bayram; Volkan Baysungur (Southern Clinics of Istanbul Eurasia, 2019)
Destroyed lung is a term used when there is disseminated destruction of the lung parenchyma caused by a chronic infectious or inflammatory pulmonary disease. Tuberculosis and bronchiectasis are the most common causes of destroyed lung described in the literature. The main hindrances to use of a videothoracoscopic (VATS) surgical approach in these cases are dense fibrotic adhesions or additional shrinkage of the thoracic cavity as a result of chronic inflammation. A 42-year-old woman presented with the complaint of intervals of hemoptysis, which had been ongoing for 6 months. Thorax computed tomography showed generalized bronchiectasis and parenchymal destruction in the right lung. A right pneumonectomy was performed via the 2-port VATS technique. This case was presented in order to demonstrate that even during a thoracotomy with adhesiolysis and difficult vessel dissection, VATS resection can be performed safely, and to highlight some of the potential intraoperative difficulties.